THERMAL STRESS PROJECTION BASED ON TEMPERATURE-HUMIDITY INDEX (THI) UNDER CLIMATE CHANGE SCENARIO - Iis Widya Harmoko; Rochdi Wasono; Tiani Wahyu Utami; Fatkhurokhman Fauzi; Iqbal Kharisudin (Jurnal Meteorologi dan Geofisika, 2023)
The degradation of green open spaces and the phenomenon of deforestation in Indonesia has increased discomfort in the region. Furthermore, if allowed to continue, the increase in temperature caused by greenhouse gases worsens the situation. Increased temperature and reduced air humidity are related to thermal stress, affecting human comfort and health. Thermal stress is measured based on the Temperature Humidity Index (THI), which calculates temperature and relative humidity variables. This study analyses THI projections under climate change scenarios RCP4.5 and RCP8.5. This study uses statistical downscaling and bias correction of Quantile Delta Mapping (QDM) to equalize the local climate. This study is divided into four 20-year periods from 2021 to 2100 to evaluate THI changes in future projections. Based on the study results, it is known that from 2041-2060, several big cities in Indonesia experienced an increase in THI and were included in the category of 50% of the population feeling uncomfortable. THI increased in the third and fourth periods. Areas that experienced a significant increase in THI were urban areas that lacked green open land and were densely populated. Surabaya City and Madura Island are the areas with the highest THI index.